WE1.8 Is colon capsule effective at reducing the requirement for colonoscopy in symptomatic patients with a faecal immunochemical test (FIT) <100? Do patients find this an acceptable investigation?. (9th August 2022) - Lord, Ian; Fajardo, Winona; Owen, Ruth; Durango, Nichole; Basavaraju, Krishna; Wells, Antonia
Abstract: Aim: To assess the effectiveness of colon capsule in reducing the need for colonoscopy and to review patient satisfaction for this investigation. Method: Potentially suitable patients for colon capsule were identified from 2 week wait referrals and patients referred to colorectal clinic. Inclusion criteria for consideration were; FIT <100, performance status 0–1 and aged 18–75. Data was collected for our first 20 patients for age, gender, FIT result, quality of the bowel preparation, pathology and the follow up outcome. Following completion of the investigation patients were invited to complete a feedback questionnaire. Results: The median age of patients was 58 (IQR 50–64) with 12 (60%) female patients. The median FIT result was <7 (IQR <7 to 33). The bowel preparation was excellent to good for 18 (90%) patients. Colon capsule was able to avoid colonoscopy for 14 (70%) patients. 6 (30%) patients required flexible sigmoidoscopy to complete the investigation or assess identified pathology. 15 (75%) patients completed patient satisfaction questionnaires, with all patients reporting little to no pain and little to no embarrassment. 9 of 13 (69%) respondents would choose to have a colon capsule again if further investigation was required. Overall patient experience was positive with a median satisfaction score 8/10 (IQR 5–10) with 10 being very satisfied. Conclusions: Our units initial experience supports the findings of other pilot studies, that the majority of symptomatic patients with a FIT <100 do not require a colonoscopy following colon capsule. Patients appear to find this an acceptable method to investigate their symptoms.